Targeting TGF-β Mediated SMAD Signaling for the Prevention of Fibrosis - Walton, Kelly L.; Johnson, Katharine E.; Harrison, Craig A. (Frontiers in Pharmacology, 2017)
Fibrosis occurs when there is an imbalance in extracellular matrix (ECM) deposition and degradation. Excessive ECM deposition results in scarring and thickening of the affected tissue, and interferes with tissue and organ homeostasis – mimicking an exaggerated “wound healing” response. Many transforming growth factor-β (TGF-β) ligands are potent drivers of ECM deposition, and additionally, have a natural affinity for the ECM, creating a concentrated pool of pro-fibrotic factors at the site of injury. Consequently, TGF-β ligands are upregulated in many human fibrotic conditions and, as such, are attractive targets for fibrosis therapy. Here, we will discuss the contribution of TGF-β proteins in the pathogenesis of fibrosis, and promising anti-fibrotic approaches that target TGF-β ligands.